2016
DOI: 10.1016/j.cortex.2016.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Cross-modal transfer of statistical information benefits from sleep

Abstract: Extracting regularities from a sequence of events is essential for understanding our environment. However, there is no consensus regarding the extent to which such regularities can be generalised beyond the modality of learning. One reason for this could be the variation in consolidation intervals used in different paradigms, also including an opportunity to sleep. Using a novel statistical learning paradigm in which structured information is acquired in the auditory domain and tested in the visual domain over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 63 publications
3
29
0
Order By: Relevance
“…Durrant and colleagues 16 showed that abstraction of the underlying statistical structure was enhanced after consolidation across sleep and predicted by the time spent in SWS. SWS also predicted a trade-off between recruitment of medial temporal lobe and striatum during subsequent use of this knowledge 8 and knowledge transfer to the visual modality 11 . In short, abstraction and generalisation performance in this task clearly benefits from sleep, particularly SWS, and therefore presents a good target for cued memory reactivation.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Durrant and colleagues 16 showed that abstraction of the underlying statistical structure was enhanced after consolidation across sleep and predicted by the time spent in SWS. SWS also predicted a trade-off between recruitment of medial temporal lobe and striatum during subsequent use of this knowledge 8 and knowledge transfer to the visual modality 11 . In short, abstraction and generalisation performance in this task clearly benefits from sleep, particularly SWS, and therefore presents a good target for cued memory reactivation.…”
Section: Introductionmentioning
confidence: 99%
“…To assess whether the effect of TMR was specific to sleep, the auditory sequence was re-presented during wakefulness directly before sleep in a third group of participants. Based on previous findings by Durrant and colleagues 8,11,16 we expected to find general overnight performance improvement, further enhanced by TMR during SWS.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations